2017
DOI: 10.5152/eurjrheum.2015.15082
|View full text |Cite
|
Sign up to set email alerts
|

Seronegative brucellosis of the spine: A case of psoas abscess secondary to brucellar spondylitis

Abstract: 185Brucellosis is an infectious disease that affects many organ systems. Osteoarticular involvement, especially spondylitis, is the most common complication of brucellosis, but psoas abscess is very rare. Serological tests at diagnosis of the disease are very valuable and most widely used. Herein, we report a case of psoas abscess secondary to brucellar spondylitis. In this case, interestingly, the serological test results were negative, and the diagnosis could be made by abscess culture. In patients, particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In one report, rapidly progressive spinal epidural abscess was observed following brucellar spondylitis, which was primarily misdiagnosed as a lumbar disc herniation[32]; delay in diagnosis and treatment were responsible for rapid progression of the disease. Another study reported a seronegative patient who developed a psoas abscess following brucellar spondylitis[33]. The basis of spondylitis diagnosis is microbiological or histopathological assessment of the tissue obtained by biopsy using a needle with computed tomography guidance.…”
Section: Osteoarticular Manifestationsmentioning
confidence: 99%
“…In one report, rapidly progressive spinal epidural abscess was observed following brucellar spondylitis, which was primarily misdiagnosed as a lumbar disc herniation[32]; delay in diagnosis and treatment were responsible for rapid progression of the disease. Another study reported a seronegative patient who developed a psoas abscess following brucellar spondylitis[33]. The basis of spondylitis diagnosis is microbiological or histopathological assessment of the tissue obtained by biopsy using a needle with computed tomography guidance.…”
Section: Osteoarticular Manifestationsmentioning
confidence: 99%
“…Spine MRI images are based on the magnetic resonance phenomenon of hydrogen in the human body, which is important to the diagnosis of common spinal diseases such as scoliosis, disc herniation, scoliosis, and disc degeneration [ 11 ]. The research of Bozbaş et al showed that MRI at this stage often showed blur and low contrast due to multiple factors [ 12 ]. Alyousef and Aldoghaither mentioned in the study of the current spine image segmentation algorithm that the watershed algorithm had inherent advantages due to its morphological characteristics.…”
Section: Discussionmentioning
confidence: 99%